Effect of climate variability on Dengue cases in Pahang - Sapuan, Isnizam; Hassan, Noor Artika; Mohd. Rus, Razman; Aidid, Edre Mohammad (IIUM Press, 2023)
Pahang is located in the eastern part of Peninsular Malaysia and experiences strong winds and heavy rainfall during the Northeast monsoon. In contrast, it encounters a dry season with high temperatures during the Southwest monsoon. This climate variability is expected to exacerbate dengue fever, a disease caused by a vector that is sensitive to climate change. Dengue is a mosquito-borne viral infection common in warm and tropical climates. Dengue is primarily transmitted by Aedes aegypti and secondarily by Aedes albopictus, causing a severe flu-like illness and sometimes may lead to a potentially lethal complication called dengue hemorrhagic fever.1 These mosquitoes are also vectors of Chikungunya, yellow fever and Zika viruses. There are four types of dengue viruses under the Flaviviridae family, namely DENV-1, DENV-2, DENV-3, and DENV-4.